Light curve and spectral modelling of the type IIb SN 2020acat. Evidence for a strong Ni bubble effect on the diffusion time - Ergon, Mattias (EDP Sciences, 2025)
We use the light-curve and spectral synthesis code JEKYLL to calculate a set of macroscopically mixed type IIb supernova (SN) models, which are compared to both previously published and new late-phase observations of SN 2020acat. The models differ in the initial mass, in the radial mixing and expansion of the radioactive material, and in the properties of the hydrogen envelope. The best match to the photospheric and nebular spectra and light curves of SN 2020acat is found for a model with an initial mass of 17 M⊙, strong radial mixing and expansion of the radioactive material, and a 0.1 M⊙ hydrogen envelope with a low hydrogen mass fraction of 0.27. The most interesting result is that strong expansion of the clumps containing radioactive material seems to be required to fit the observations of SN 2020acat both in the diffusion phase and in the nebular phase. These Ni bubbles are expected to expand due to heating from radioactive decays, but the degree of expansion is poorly constrained. Without strong expansion, there is a tension between the diffusion phase and the subsequent evolution, and models that fit the nebular phase produce a diffusion peak that is too broad. The diffusion-phase light curve is sensitive to the expansion of the Ni bubbles because the resulting Swiss-cheese-like geometry decreases the effective opacity and therefore the diffusion time. This effect has not been taken into account in previous light-curve modelling of stripped-envelope SNe, which may lead to a systematic underestimate of their ejecta masses. In addition to strong expansion, strong mixing of the radioactive material also seems to be required to fit the diffusion peak. It should be emphasized, however, that JEKYLL is limited to a geometry that is spherically symmetric on average, and large-scale asymmetries may also play a role. The relatively high initial mass found for the progenitor of SN 2020acat places it at the upper end of the mass distribution of type IIb SN progenitors, and a single-star origin cannot be excluded.